Banking on Bonds: The New Links Between States and Markets1. (12th October 2015) - Gabor, Daniela; Ban, Cornel
Abstract: This article examines a neglected structural transformation in European finance: the growing importance of government debt as collateral for Europe's repo markets, where banks borrow cash against collateral. Seduced by the promises of repo market‐driven financial integration, the EU institutions and Member States encouraged private finance to generate its own architecture for the European repo market in the early years of the euro, sidelining known problems about systemic fragilities. These fragilities materialized after Lehman Brothers' collapse and were exacerbated by the ECB's collateral policies. The European sovereign debt crisis shows that governments, just like private asset issuers, can rapidly become vulnerable to repo pro‐cyclicality and collateral crises.